Drug Resistant Fetal Arrhythmia in Obstetric Cholestasis - Nahide Altug; Ayse Kirbas; Korkut Daglar; Ebru Biberoglu; Dilek Uygur; Nuri Danisman (Case Reports in Obstetrics and Gynecology)
Obstetric cholestasis (OC) is a pregnancy specific liver disease characterized by increased levels of bile acid (BA) and pruritus. Raised maternal BA levels could be associated with intrauterine death, fetal distress, and preterm labor and also alter the rate and rhythm of cardiomyocyte contraction and may cause fetal arrhythmic events. We report a case of drug resistant fetal supraventricular tachycardia and concomitant OC. Conclusion. If there are maternal OC and concomitant fetal arrhythmia, possibility of the resistance to antiarrhythmic treatment should be kept in mind.